"Buy-It-Now" Purchasing in Online Auctions: a Transaction Value Perspective - Bansal, Nitin (Auckland University of Technology, 2018)
This study provides important theoretical and practical insights into consumers’ intentions to shop in online auctions using the Buy-It-Now (BIN) option. The BIN option enables buyers and sellers to transact instantly without going through the lengthy auction process. The extant literature on consumer behaviour in online auctions provides a general understanding of consumers’ BIN purchase choices, without revealing how consumers form their evaluations of the attractiveness of the “deal”. Prior studies have not addressed the link between deal attractiveness and BIN purchasing. To address this gap, this study builds on the concept of transaction value, that is, perceived deal attractiveness (Thaler, 1985). The study identified one monetary factor (“perceived monetary price”) and two nonmonetary factors (“perceived risk”, and “perceived time and effort”) relevant to consumers’ perceived transaction value and purchase intentions for BIN offers. To examine the influence of each of these factors on consumers’ perceived transaction value and BIN purchase intentions, respectively, a full-profile conjoint analysis (decompositional technique) was used. In addition, path analysis (compositional technique) was used to examine the direct and mediating influence of perceived transaction value on consumers’ BIN purchase intentions. Data was collected by employing and administrating a pre-tested survey via a consumer panel (n = 212). The survey comprised three sections. Section One filtered out respondents who had not shopped in online auctions in the past 12 months or had no prior BIN purchasing experience. Section Two presented respondents with a scenario of buying a smartphone as a birthday gift for a sister. For this, they were to go through 12 conjoint treatment profiles (one by one) for the smartphone and rate their feelings about the BIN price offer and purchase intentions with respect to each profile. Section Three captured respondents’ demographic characteristics. The findings of the conjoint analysis revealed that consumers’ perceived transaction value for BIN offers was driven predominantly by their perceived risk (as expressed by seller experience and reputation) (66%), followed by perceived monetary price (22%), and perceived time and effort (as expressed by auction duration) (12%), respectively. This pattern was similar for consumers’ BIN purchase intentions which were again driven predominantly by consumers’ perceived risk (71%), followed by perceived monetary price (20%), and perceived time and effort (9%). The findings of the path analysis revealed that consumers’ perceived transaction value significantly influenced (88% variation) BIN purchase intentions. The mediating influence of perceived transaction value was significant. In terms of theoretical and practical implications, the findings suggest that no matter how attractive a BIN deal is compared to regular market prices, there is expected to be far less likelihood of consumer acceptance of the deal if a seller’s overall reputation is also not positive enough. Consumers associate higher perceived transaction value and subsequent purchase intentions for BIN offers with experienced and reputed sellers rather than inexperienced and less reputed sellers. It is recommended that relatively experienced and reputed sellers are better off setting premium BIN prices.
Keywords: Online auctions; Buy-it-now (BIN); Transaction value; Perceived monetary price; Perceived risk; Perceived time and effort; Purchase intentions